Mediating Indonesian Islamic Center in the Era of Post-Islamism - Purnama Hidayaturrahman; Holy Rafika Dhona (Asian Journal of Media and Communication, 2020)
Islamic centers emerged when Muslims in the West had difficulties to build a mosque. As a majority, Indonesian Muslim communities do not need to adopt the concept of Western Islamic Center.  Nevertheless, establishing Islamic Center is quite popular among Indonesian Muslims. This paper argues that the establishment of Islamic Center is a practice of post-Islamism in Indonesia, in which Islam is interpreted in a specific way that juxtaposes religiosity and leisure, mixes between ‘the sacred’ and ‘the profane’. Taking the Mataram Islamic Center as a case study, this study explores how discourse of the Islamic Center shapes its establishment. Applying critical discourse analysis, this study takes several units of analysis, i.e. the mediation practices of the center and the visiting practices of the visitors. This study finds that there are two prominent discourses, namely the center as a religious space and the center as a tourist space, both of which do not defeat each other. Keywords: Islamic center, critical discourse analysis, post-Islamism, space mediation.